Perceptions of knowledge, attitude and skills about non-suicidal self-injury: A survey of emergency and mental health nurses - Ngune, Irene; Hasking, Penelope; McGough, Shirley; Wynaden, Dianne; Janerka, Carrie; Rees, Clare (Wiley-Blackwell, 2020)
Non-suicidal self-injury (NSSI) is a major public health concern and is also associated with increased risk of suicide. The type of care people with NSSI receive at the hospital impacts their health outcomes. This study explored emergency department (ED) and mental health nurses’ (MHNs) understanding, attitudes, empathy and confidence to work with people presenting with NSSI. ED and MHNs who belonged to either the College of Emergency Nursing Australasia (CENA) or the Australian College of Mental Health Nurses (ACMHN) were invited to complete an online survey through a group email from their college. One hundred and one nurses (56 ED and 45 MHNs) completed the survey. The results revealed that nurses from both groups had an accurate understanding of NSSI and had positive attitudes about patients who self-injure. However, confidence was higher among MHNs. Greater knowledge of NSSI was correlated with increased confidence, positive attitudes and empathy. For mental health nurses, but not ED nurses, years of clinical practice was associated with nurses’ confidence. In contrast, ED nurses with more than 10 years’ experience were less confident in addressing NSSI than ED nurses with less experience. Issues that affect both ED and MHNs’ knowledge, attitude, empathy and confidence to care for patients who self-injure are multifactorial. Future education and training should focus on therapeutic interactions with people at risk of repeat NSSI. Further, more research is recommended to explore patients’ perspectives of nurses’ attitudes in care for people who self-injure.